Ultrasonographic changes in fetal gastrointestinal motility during the last ten days before parturition in dogs - Siena, Giulia; Romagnoli, Stefano; Drigo, Michele; Contiero, Barbara; di Nardo, Francesca; Milani, Chiara (Frontiers in Veterinary Science, 2022)
Fetal gastrointestinal motility (FGM) was suggested as useful to assess fetal maturity. The aim of our study was to quantify FGM in relation to days before parturition (dbp), maternal size and sex ratio of pups. Twenty-three 2-9-year-old and 3.5-56.8 kg body weight clinically healthy pregnant bitches of 16 different breeds were monitored twice during the last 10 days of pregnancy. Fetal intestine was observed in longitudinal and transversal scan on 3 of the most caudal fetuses in both uterine horns. Gestational age was counted backward from parturition day. Number of fetuses showing FGM was recorded in time I (-11/-5 dbp) and II (-4/0 dbp). Mann-Whitney test was performed to analyze variations of FGM% in relation to time and parity. Kruskal-Wallis test was performed to identify variations of FGM% in relation to maternal size and sex ratio. Statistical significance was set at α = 0.05. A total of 147 FGM observations on 50 ultrasonographic monitoring points were performed. FGM% was higher during time II compared to time I (median: 33%, range 0 - 100% vs 100%, range 33 - 100%; P < 0.0001). FGM% was higher in small compared to large size bitches (median: 100%, range 67 - 100% vs 67%, range 0 - 100%; P = 0.01). FGM% was not affected by parity and sex ratio. As previously reported, a significant increase in FGM% was observed in the last 5 dbp. FGM observation may be influenced by maternal size, with easier evaluation in small size bitches, as well as ultrasound equipment and positioning.